Stanford-Binet Intelligence Scale Form L-M Predictive Power on Academic Achievement - Reinaldi, Eugenius Tintus; Hidayat, Rahmat (FAKULTAS PSIKOLOGI UIN SYARIF HIDAYATULLAH JAKARTA, 2021)
Stanford-Binet Intelligence Scale Form L-M test is widely used in Indonesia to assess the academic capacity of elementary school students. However, its predictive power upon academic achievements has not been examined. This research represents a preliminary attempt at closing this gap. Stanford-Binet scores obtained 1 to 3 years earlier were used to explain variations in three subject marks of 156 an Elementary School from the 3rd, 4th, and 5th Grades. Simple regression analysis shows that 4.3% to 25.4% of the variance can be explained by Stanford-Binet scores, indicating a low to moderate predictive power. The results suggest a limited predictive power of the Stanford-Binet Form L-M test for applications in the assessment of the academic capacity of elementary school children.